Modification of Soil Used in Core of Earth Dams - ., Hassan A. Omran; ., Noura B. Ibraheem (Iraqi Journal of Civil Engineering, 2018)
The earth-fill dams are simple structures which are able to prevent the sliding and overturning because of their self-weight. Due to lack of suitable clay materials, the dams may be designed as zoned core which is composed of three vertical zones contains central impermeable core and two permeable shells on their two sides of the core. Impervious core is used in zoned earth dam to reduce the quantity of seepage through the body of the dam and to relief part of risk of piping and erosion in the downstream side. This study aims to study the soil properties that is used as a core of earth dam through a series of laboratory experiments that were carried out a several soil samples mixed with both lime and silica fume, in order to stabilize the soil. The process of stabilization aims to increase the soil strength and reducing its permeability and compressibility. Test results show that adding lime and silica fume to the soil decreases the permeability of soil with different cases of study, the percentage of decreases in case of standard compaction about (21%-90%) while in modified compaction test the permeability decreases in range (41.7%-91.3%). Also the unconfined compressive strength of the soil increasing significantly in both cases of compaction which were standard and modified. When add the materials, these values were increased in range (76%-90%) for samples from standard compaction test, while it being (0.21%-42%) in modified compaction test.